Tanggung Jawab KONI dalam Hal Pemberian Intensif Bagi Atlet Panah di Kabupaten Barito Selatan - Rahman, Ferdy; Murtadho, Ali; Angelia, Novita Mayasari (LPPM Institut Pendidikan Nusantara Global, 2025)
The Indonesian National Sports Committee (KONI) plays an important role in developing and fostering athletes across various sports, including archery in South Barito Regency. Providing incentives to athletes is a form of support aimed at improving their performance and motivation in competition. This article discusses KONI’s responsibilities regarding the provision of incentives for archery athletes in South Barito Regency, including the distribution mechanism, eligibility criteria, and the impact of incentives on athletes’ achievements. This analysis is expected to provide a clear overview of KONI’s role in supporting archery athletes as well as offering recommendations for improving the incentive distribution system in the future. The Indonesian National Sports Committee (KONI) plays an important role in developing and fostering athletes across various sports, including archery in South Barito Regency. Providing incentives to athletes is a form of support aimed at improving their performance and motivation in competition. This article discusses KONI’s responsibilities regarding the provision of incentives for archery athletes in South Barito Regency, including the distribution mechanism, eligibility criteria, and the impact of incentives on athletes’ achievements. This analysis is expected to provide a clear overview of KONI’s role in supporting archery athletes and provide recommendations for improving the incentive system in the future.